Foliage pests of Marula (Sclerocarya birrea) in Malawi: susceptibility of different provenances - Msukwa, V.; Munthali, C.; Nyoka, B.; Missanjo, E.; Kamanga, M.; Graziosi, I.; Msiska, V. (Springer, 2021)
Knowledge of insects’ damage to Agroforestry species is prerequisite prior to promotion of domestication of the species. The study was conducted to assess foliage insect pests in 21 Sclerocarya birrea provenances. Assessment parameters included tolerance levels, tree canopy position of attack, mode of leaf defoliation and type of insect pests responsible for the damage. The results revealed that highly tolerant provenances to leaf defoliation included Kalanga, Magunde, Moamba, and Marracuene. Highly susceptible provenances comprised of Chikwawa, Rumphi, Ntcheu, Missira and Mangochi. Highly significant (P < 0.001) variations existed in tree damage basing on crown position. The top canopy was the most affected followed by the middle and bottom canopies. Leaf damage was found to be significantly (X2 = 4.989, P = 0.026) associated with fruit production, and leaf damaged trees were found to produce three times (Odds Ratio = 3.2) less fruits compared to undamaged tree leaves. The most dominate form of leaf damage was defoliation (43%), followed by skeletonizing (18%). The least leaf damage trees were 37%. Leaf defoliators comprised of two orders namely Coleoptera (beetle) and Lepidoptera (caterpillar). Ceratitis (Pterandrus) capitata (fruit flies) were the most destructive to mature fruits. Although not the primary objective of the study, Ceratitis (Pterandrus) capitata (fruit flies) was identified as the major pest of Marula fruits. Future provenance or progeny trials should be replicated across different ecological areas in order to assess genotype-by-environment interaction effects resulting from differences in leaf flushing period.